Perancangan Model Sistem Informasi Tuberkulosis Paru Terintegrasi Berbasis Web - Gandha Sunaryo Putra; Evy Hariana (Jurnal Vokasi Kesehatan, 2019)
Abstract: Design of Web-Based Integrated Pulmonary Tuberculosis Information Model. Pulmonary TB is one of the health problems in Sintang District where in 2016 Pulmonary TB Case Notifcation Rate (CNR) is 100/100,000 population. An important step that must be carried out by the Sintang District Health Office is to evaluate the Pulmonary TB program. Based on preliminary studies, the evaluation of the Pulmonary TB control program is still not working properly. This is because the data management process is still done manually so that reports are often late. Therefore, the need for an appropriate information system model and in accordance with the needs of TB program users to support the evaluation of the Pulmonary TB program. The purpose of this study was to design a web-based integrated pulmonary TB information system model to support the evaluation of Pulmonary TB programs. This research is a qualitative research. Subjects in this study were all users of the TB information system consisting of Head of Division, Section Head, TB Wasor, TB Staï¬€ in Health Service and several managers of Pulmonary TB programs. The results of this study were obtained a design model of integrated WEB-based TB information system based on the needs and desires of system users. Sintang District Health Office is recommended to build a system that has been designed based on the needs of system users so that the problem of the TB information system can be overcome.Â Abstrak: Perancangan Model Sistem Informasi Tuberkulosis Paru Terintegrasi Berbasis Web. TB Paru merupakan salah satu permasalahan kesehatan di Kabupaten Sintang yang pada tahun 2016 memiliki Case Notifcation Rate (CNR) sebesar 100/100.000 penduduk. Langkah penting yang harus dilakukan oleh Dinas Kesehatan Kabupaten Sintang adalah melakukan evaluasi program TB Paru. Kegiatan evaluasi program penanggulangan TB Paru masih belum berjalan sebagaimana mestinya. Hal ini disebabkan proses pengelolaan data masih dilakukan secara manual sehingga laporan sering terlambat. Oleh karena itu, perlu dikembangkan suatu model Sistem Informasi yang tepat serta sesuai dengan kebutuhan pengguna program TB guna mendukung evaluasi program TB Paru. Tujuan penelitian ini adalah untuk merancang model Sistem Informasi Tuberkulosis Paru terintegrasi berbasis Web untuk mendukung evaluasi program TB Paru. Penelitian ini merupakan penelitian kualitatif. Subjek dalam penelitian ini adalah semua pengguna Sistem Informasi TB yang terdiri dari Kepala Bidang, Kepala Seksi, Wasor TB, Staf TB Dinas Kesehatan dan beberapa pengelola program TB Paru. Penelitian ini menghasilkan suatu model rancangan Sistem Informasi TB terintegrasi berbasis WEB berdasarkan kebutuhan dan keinginan dari pengguna sistem. Disarankan kepada Dinas Kesehatan Kabupaten Sintang untuk membangun sistem yang sudah dirancang berdasarkan kebutuhan dari pengguna sistem sehingga permasalahan Sistem Informasi TB bisa diatasi.